The effect of professional skepticism, client pressure, auditor experience, and audit regulation on audit fraud (Empirical study in Headquarter Office of Badan Pemeriksa Keuangan RI) - Warsidi Warsidi; Siti Maghfiroh; Larasati Nanda (Jurnal Ekonomi Bisnis dan Akuntansi (JEBA), 2018)
Badan Pemeriksa Keuangan is a state institution authorized to audit reports on the management and accountability of state finances to the Central Government, Regional Government, Bank Indonesia, State-Owned Enterprises, Public Service Bodies, and Regional-Owned Enterprises. In carrying out its duties, BPK has several authorities that are BPK examine the object of examination, plan and conduct an inspection, determine the time and method of examination, and compile and present the report of the examination result. Based on the 1945 Constitution, BPK is an independent state institution so that in carrying out its duties, BPK perform independently and freely without any parties that can interfere or influence the examination report. But in fact, there are still many phenomena in which auditors conduct audit fraud by selling buying audit opinions and bribes to change the contents of the examination report. There are several factors that lead to audit fraud, such as professional skepticism, client pressure, auditor experience, and audit regulation. This study aims to examine the effects of professional skepticism, client pressure, auditor experience, and audit regulation on audit fraud. This research is a quantitative study with primary data from questionnaires distributed to BPK with respondents AKN II, III and IV. Sampling technique uses a convenience sampling method. Data analysis technique used is multiple regression analysis. The results of this study indicate that professional skepticism and audit regulation have a significant negative effect on audit fraud, the auditor's experience has a negative insignificant effect on audit fraud, while client pressure has an insignificant positive effect on audit fraud.Keywords: professional skepticism, client pressure, auditor experience, audit regulations, audit fraud.